Association of neck pain and low back pain with dysfunctional breathing and stress - Abdul Rehman; Batool, Fouzia; Hassan Saeed; Faiza Batool (Journal of the Pakistan Medical Association, 2026)
Objective: To assess and associate neck pain and low back pain with dysfunctional breathing and stress. Method: The cross-sectional study was conducted at the Department of Rehabilitation Sciences, Shifa Tameer-e-Millat University and Capital Hospital, Islamabad, Pakistan, from October 2022 to January 2023, and comprised adult patients having neck pain in group A1, and those with back pain in group A2. Healthy age-matched controls were enrolled in groups B1 and B2. Data was collected using the Roland Morris Questionnaire, the Neck Disability Index and the Perceived Stress Scale regarding low back disability, neck disability, and stress levels, respectively. Dysfunctional breathing was measured using the Self-Evaluation Breathing Questionnaire and Contec Spirometer SP-10. Data was analysed using SPSS 22. Results: Of the 256 subjects, 64(25%) were in each of the four groups. Overall, there were 130(50.8%) males and 126(49.2%) were females, and the age of the subjects ranged aged 18-44 years. Patients in groups A1 and A2 scored higher on the Self-Evaluation Breathing Questionnaire and the Perceived Stress Scale than those in groups B1 and B2 (p<0.05). Spirometric measures were significantly lower in groups A1 and A2 than the control groups (p<0.05). Self-Evaluation Breathing Questionnaire showed moderate positive correlation with neck disability(p<0.05), but only a weak correlation with neck and low back pain, while spirometric values were negatively correlated with both pain and disability(p>0.05). Conclusion: Dysfunctional breathing was more prevalent in individuals with neck and low back pain than healthy individuals. Furthermore, increased neck pain, low back pain and disability were linked to dysfunctional breathing and stress. Key Words: Breathing, Cervical pain, Disability, Lumbar pain, Stress.